Scientific production of nursing in the perspective of oral history: an integrative review - Maria de Jesus Lopes Mousinho Neiva, Benevina Maria Vilar Teixeira Nunes, Juliana Vieira Figueiredo, Amália de Oliveira Carvalh (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v2i3.908